A system dynamics model for industrial carbon emissions in Baoding. Issue 6 (1st November 2016) - Wen, Lei; Bai, Lu; Zhang, Ernv; Weng, Jianfeng
ABSTRACT: Baoding, as one of the first batch of low-carbon pilot cities and heavily industrial energy consumers, faces more responsibilities to adjust industrial structure and mitigate carbon emissions. The purpose of this study is aimed at predicting and comparing industrial carbon emissions of Baoding in 11 scenarios under different policy focus, and then providing emission-cutting recommendations. In view of various scenarios issues, system dynamics has been applied to predict and simulate. To begin with, the model has been established following the step of causal loop diagram and stock flow diagram. Moreover, before we employ the model to predict and simulate, historical test is adopted via the comparison of simulated data and historical data in 2005–2013. Besides, this paper decomposes scenarios factors into energy structure, high-energy-consumption enterprises and growth rate of industrial output. The simulation results show that the prospect of carbon-emission issues in Baoding is not cheerful. Hence, some recommendations about low-carbon mode in Baoding's industrial carbon emissions have been proposed according to simulation results.